Effects of anti-inflammatory therapy on bursting pressure of colonic anastomosis in murine dextran sulfate sodium induced colitis. (August 2014) - Myrelid, Pär; Salim, Sa'ad Y.; Darby, Trevor; Almer, Sven; Melgar, Silvia; Andersson, Peter; Söderholm, Johan D.
Abstract Background. The aim of this study was to examine the effect of colitis and anti-inflammatory therapies on the healing of colonic anastomoses in mice. Methods. Female C57BL/6 mice were randomized into eight groups; four groups receiving plain tap-water and four groups receiving dextran sulfate sodium. Intra-peritoneal treatment was given therapeutically for 14 days with placebo, prednisolone, azathioprine, or infliximab (IFX). Colonic anastomoses were performed and bursting pressure (BP) measurements were recorded and the inflammation evaluated with histology and zymography. Results. The mice with colitis had a more active inflammation based on histology and bowel weight compared with the tap water group, 8.3 (7.6–9.5) mg/mm and 5.5 (4.8–6.2) mg/mm respectively (p < 0.0001). Similarly mice with colitis receiving placebo had a more active inflammation, 12.8 (10.6–15.0) mg/mm, which differed significantly from all the other therapy arms among the colitic mice; prednisolone 8.1 (7.5–9.1) mg/mm (p = 0.014), azathioprine 8.2 (7.0–8.5) mg/mm (p = 0.0046), IFX 6.7 (6.4–7.9) mg/mm (p = 0.0055). BP for the placebo group was 90.0 (71.5–102.8) mmHg and did not differ from azathioprine or IFX groups, 84.4 (70.5–112.5) and 92.3 (75.8–122.3) mmHg respectively. In contrast BP for the prednisolone group was significantly decreased compared to placebo, 55.5 (42.8–73.0) mmHg (p = 0.0004). Conclusions. All therapies had a beneficial effect on the colitis. An impaired BP of colonic anastomoses was noted after preoperative steroids but not after azathioprine or IFX in this model.